(untitled) (Annals of Medical Research, 2021)
Aim: There is no standard treatment for corticosteroid refractory acute and chronic graft versus host disease (GVHD). Ruxolitinib and extracorporeal phopheresis (ECP) are promising treatment options in GVHD. In this study, we aimed to share our clinical experience in steroid refractory GVHD patients treated with ruxolitinib plus ECP. Materials and Methods: The data of patients receiving ruxolitinib plus ECP for corticosteroid refractory acute and chronic GVHD patients were analyzed retrospectively. Results: A total of 11 cases, 6 of which were acute, were included in this retrospective, observational and single-center study. Acute GVHD developed in the 6 patients after allogeneic HSCT (median onset of GVHD=27, between 20 and 60 days ). Chronic GVHD developed in the 5 patients after allogeneic HSCT (median onset of GVHD= 159 between 60 and 380 days. The overall response rate of acute GVHD patients to ruxolitinib ECP combination therapy was 16.7% (complete response: 16.7%, partial response: 0%). The overall response rate of chronic GVHD patients to combination therapy was 60% (complete response: 20%, partial response: 40%). As a result of combination therapy, thrombocytopenia occurred in 36% (4/11) of patients, neutropenia in 27% (3/11) of patients, and CMV reactivation in 9% (1/11) of patients. Conclusion: We observed a low rate of overall response to ruxolitinib plus ECP treatment in acute GVHD patients but a high rate in chronic GVHD patients. According to our trial, ruxolitinib ECP combination may be beneficial in GVHD, especially in chronic GVHD, but prospective trials comparing its efficacy with other agents are needed.